Surface integrity of Mg-based nanocomposite produced by Abrasive Water Jet Machining (AWJM). Issue 15 (18th November 2017) - Mardi, K. Bimla; Dixit, A. R.; Mallick, A.; Pramanik, Alokesh; Ballokova, Beata; Hvizdos, Pavol; Foldyna, Josef; Scucka, Jiri; Hlavacek, Petr; Zelenak, Michal
ABSTRACT: This paper investigates the influence of jet traverse speed on the surface integrity of 0.66 wt% Al2 O3 nanoparticle reinforced metal matrix composite (MMC) generated by Abrasive Water Jet Machining (AWJM). Surface morphology, surface topography, and surface roughness (SR) of the AWJ surface were analyzed. The machined surfaces of the nanocomposites were examined by laser confocal microscope and field emission scanning electron microscope (FESEM). Microhardness and elasticity modulus measurement by nanoindentation testing were also performed across thickness of the samples to see depth of the zone, affected by AWJ cutting. The result reveals that extent of grooving by abrasive particle and irregularity in AWJ machined surface increases as the traverse speed increased. Similarly, the rise in value of surface roughness parameters with traverse speed was also seen. In addition, nanoindentation testing represents the lower hardness and elastic modulus due to softening occurs in AWJ surface.